Chapter 2 Developing Twenty-First-Century Design Professionals through Impactful Curricula - Meth, Deanna; Brough, Dean (Intellect, 2024)
There has been a systemic shift in contemporary design professions, with the concomitant need for placing the requisite 21st-century skills and capabilities for such professions at the forefront of curriculum design. This chapter describes the development of a new Bachelor of Design curriculum which, drawing on internal and external stakeholder needs and sound educational precepts, includes a suite of transdisciplinary Impact Lab units, titled Place, People, Planet and Purpose. Alongside specialisation in one of seven disciplines, labs form a compulsory part of the curriculum - discrete yet linked units of study scaffolded across the program and designed to engender transdisciplinarity in authentic design contexts. Whilst the charter for the Labs is robust, the challenges of delivering such units are also outlined. A clear case is made for links between transdisciplinarity and ‘impact’ in the curriculum within a future-focused narrative of ethical, responsible and transformational design for positive global change.